THE STABILITY OF THE ACID-BASE EQUILIBRIUM OF THE BLOOD IN NATURALLY NEPHROPATHIC ANIMALS AND THE EFFECT ON RENAL FUNCTION OF CHANGES IN THIS EQUILIBRIUM : I. A STUDY OF THE ACID-BASE EQUILIBRIUM OF THE BLOOD IN NATURALLY NEPHROPATHIC ANIMALS AND OF THE FUNCTIONAL CAPACITY OF THE KIDNEY IN SUCH ANIMALS FOLLOWING AN ANESTHETIC. - MacNider, William deB. (The Rockefeller University Press, 1918)
1. The naturally acquired chronic glomerulonephropathies of the dog are not due to an acid intoxication. 2. Such an injury renders the acid-base equilibrium of the animal unstable and susceptible to an agent such as an anesthetic which tends to induce an acid intoxication. 3. When naturally nephropathic animals are anesthetized by Grehant's anesthetic, the principal anesthetic ingredient of which is chloroform, the animals develop an acid intoxication, and become anuric and non-responsive to diuretic substances. 4. The development of the anuria has been constantly associated with swelling, vacuolation, and necrosis of the convoluted tubule epithelium. 5. In the kidneys of these animals there occurs an accumulation of fat which is largely confined to the ascending limbs of Henle's loops and which shows a quantitative relation with the degree of acid intoxication.